Caracterización de los grupos de investigación en el área de odontología registrados en Colciencias a diciembre de 2012 - Pieschacón-Gutiérrez, María Paulina; Rodríguez-Gómez, Martha Juliana; Concha-Sánchez, Sonia Constanza (Revista Facultad de Odontología Universidad de Antioquia, 2014)
Introduction: the goal is to characterize the dentistry research groups registered in Colciencias. Methods: this was a descriptive observational study using the institutional platform to find information on groups, researchers, and the products of research projects. The information was systematized in Excel and processed in Stata 9.0. The univariate statistical analysis calculated summary measures according to the nature of variables. The bivariate statistical analysis related the “categorization of groups” output variable with the other variables, by means of the X2 test and Fisher’s exact test for the qualitative variables, and the ANOVA test or Kruskal-Wallis test for the quantitative ones, considering a level of significance of p < 0.05. Results: 52 groups were identified; 13.5% of them belonged to category A and 34.6% to category D. 63.4% of the groups have focused on clinical areas, and scientific articles were the most commonly used means for knowledge dissemination. Conclusion: dentistry research groups have reached a good level of development in Colombia, considering the bibliometric indicators defined by Colciencias. However, they tend to be traditional in terms of the topics they approach. Their impact on the needs of oral health of Colombian population is questioned, especially concerning those populations in situations of vulnerability. In addition, the categorization of groups was strongly influenced by the economic trends in scientific production and the dental market dominating the profession.